COMBINING ENGLISH VIDEO DUBBING WITH CONTEXTUAL INSTRUCTION IN ENHANCING ENGLISH-SPEAKING SKILL OF SECOND GRADE AT SMA NEGERI 8 MAROS - Krisna Rifky Perdana; Badruddin Kaddas; Jusmaniar N (ADHILINGUA: Journal of Language Education, Lilnguistics and Literature, 2025)
The objective of this study is to find out how the combining English video dubbing with contextual instruction to improving students' English-Speaking Skills in second grade of SMAN 8 Maros. The research employed Quasi Experimental model with a Nonequivalent Control Group Design, Comprising Two Groups: The Control Group and the Experimental Group. The instrument of this research is recording and test (pretest and posttest). The data analysis is descriptive analysis and descriptive inferential analysis. The data of pretest revealed a standard deviation is 1.309 from the experimental group and 1.264 from the control group. The posttest experimental group demonstrated a standard deviation is 1.591, while the posttest control group exhibited a standard deviation is 1.161. Substantiated results of the normality test indicate the control class pretest was 0.010 and the control class posttest was 0.018. Given the significance value is greater than 0.05, It therefore follows the data is normally distributed. The result found at the t count obtained is 7.217, followed by finding the t table obtained according to the df value of 67 while the sig level value is 0.05/2 = 0.025 and t table of 1.995. These results show the score of t test 7.127 > t table 1.996. At 5% significance, it means that there is a difference between the speaking skills of students who use the technique of combining English video dubbing with contextual instruction and those who do not use the technique, and sig value (2-tailed) of 0.001 <0.05 means the combining English video dubbing with contextual instruction has effect on the improving students’ English speaking skill in second grade of SMA Negeri 8 Maros.